Characteristics of Agricultural and Plantation Wastes as Solid Biomass Energy Feedstock: A Systematic Review - Tambunan, Hardiansyah; Safrizal; Fahmi, Mutiara (Jurnal Konversi Energi dan Manufaktur, 2025)
The conversion of agricultural and plantation waste into biomass energy represents a promising pathway in the global transition to environmentally friendly energy sources. However, systematic comparisons of different types of agricultural and plantation biomass waste remain limited. This study aims to identify and evaluate the characteristics of various agricultural and plantation wastes to determine their feasibility as solid biomass energy feedstock. A systematic literature review was conducted using databases such as PubMed, DOAJ, and manual searches, focusing on articles published between 2014 and 2025. A total of 32 relevant studies were selected based on inclusion criteria. The analysis revealed that coconut shells, coffee grounds, and oil palm kernel shells possess superior fuel properties, particularly high calorific values of ≥ 4000 cal/g, making them highly suitable for solid biofuel production. These findings emphasize the strategic potential of agricultural and plantation waste as a sustainable energy source. The study contributes to the advancement of circular economy practices, promotes effective waste management, and supports the achievement of Sustainable Development Goals (SDGs).